ダイ44ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 2003 - 江崎, 雄治; エサキ, ユウジ; 杉田, 興正; スギタ, オキマサ; 鳥井, 克彦; トリイ, カツヒコ; 高橋, 武; タカハシ, タケシ; 安達, 正樹; アダチ, マサキ; Esaki, Yuji; Sugita, Okimasa; et al. (2007)
P(論文) この報告は,第44次南極地域観測隊気象部門が,2003年2月1日から2004年1月31日まで昭和基地において,及び2003年2月1日から2004年1月20日までドームふじ観測拠点において行った気象観測結果をまとめたものである.観測方法,測器,統計方法等は第43次隊とほぼ同様である. 越冬期間中,特記される気象現象として,次のものが挙げられる.1) 昭和基地での年平均気温は-9.0℃で観測史上第2位の高さであった.また,年合計雪日数は第1位の多さであった.2) 南極昭和基地上空におけるオゾン全量は,8月中旬にオゾンホールの目安である220 m atm-cm以下の値を観測した後,9月から10月にかけて過去最低レベルで推移した.6,9月は月平均値としては過去最も少なかった.2003年のオゾンホールは,欠損量(破壊量)が過去最大,面積が過去2位であり,例年よりも発達時期が早かった.3) ドームふじ観測拠点における越冬期間(2003年2月～2004年1月)の平均気温は-53.8℃,最低気温は7月23日に観測した-79.6℃であった. This report describes the results of meteorological observations at Syowa Station from February 1st, 2003 to January 31st, 2004, and at Dome Fuji Station from February 1st, 2003 to January 20th, 2004, carried out by the Meteorological Observation Team of the 44th Japanese Antarctic Research Expedition (JARE-44). The observation methods, instruments and statistical methods used by the JARE-44 were almost the same as those used by the JARE-43 observation team. Remarkable weather phenomena observed during the period of JARE-44 are as follows.1) Annual mean surface temperature in 2003 at Syowa Station was-9.0℃, which was the second highest value in the historical record of Syowa Station. The number of snow days in 2003 at Syowa Station was 233 days, which set a record at Syowa Station.2) The amount of total ozone over Syowa Station became lower than or equal to 220 m atm-cm in mid-August, and was close to the minimum levels from September to October. The monthly means of total ozone in June and September at Syowa Station were the lowest values since the beginning of monitoring. The ozone hole in 2003 appeared earlier than usual. The annual maximum in the ozone mass deficiency and the ozone hole area were the second largest and the largest, respectively.3) The mean surface temperature in the wintering period (Feb., 2003-Jan., 2004) at Dome Fuji Station was-53.8℃; the lowest temperature was-79.6℃ observed on July 23rd. departmental bulletin paper